Enforced Gender Performativity and Objectification of Women by Society in Han Kang’s The Vegetarian - Thapa, Mumaya (Kalika Journal of Multidisciplinary Research, 2025)
Human bodies have been associated to different roles by society on the basis of their body anatomy. A female body has been assigned to the feminine roles prescribed by patriarchal society. The protagonist of Han Kang’s The Vegetarian (2018), Yeong-hye denies to cook and eat meat which is an essential part of her culture. Her decisions and actions are perceived as abnormal, thus subjected to correction. This study examines the role of traditional gender norms in objectification of women in the novelemploying Judith Butler’s theory of gender performativity and Fredrickson and Roberts’s theory of objectification as the modes of inquiry. It reveals that Yeong-hye falls victim to traditional gender roles and becomes an object to her husband, family and society. Her husband, father and brother-in-law perceive her as a body rather than a complete human being with her own subjectivity. Yeong-hye’s abstinence from carnivore diet and sexual relationship with her husband leads to her abandonment and alienation from the society. The continuous pressure on her to fit in the conventional norms results in deterioration of her physical and mental health. When Yeong-hye is compelled to fit in stereotypical roles, she is objectified and deprived of her subjectivity. Her body has been understood as an object and expected to operate according to the conventions of society. This paper concludes that strict rules of gender performativity lead to loss of subjectivity and objectification of women.